Features of the Color Scheme in the Design of Student Residential Complexes (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
The purpose of this article is to correctly select a color solution when designing student dormitory complexes, and the research methods on the topic of the article are formed from a systematic analysis that allows you to consider the color solution factors of object formation and development in an interrelated way. The results of the article are a summary of the goals and objectives achieved for the living environment in student dormitory and through the use of color, and the color solution for creating a comfortable environment in educational, work and recreation rooms relevant to the mental work of the modern student dormitory object.